Collaborative concept mapping in team-based learning: synthesizing complex immunology concepts in medical education - Baxa, Dwayne M.; Taylor, Tracey A. H.; Cortes, Claudio; Kemp, Kyeorda (Frontiers in Education, 2025)
IntroductionTeaching immunology to first-year medical students is challenging due to the complexity of the immune system's interactions with pathogens and other organs systems. One solution is to integrate immunology with different topics. To address this challenge, we developed a modified team-based learning (TBL) session that incorporated collaborative concept mapping to assess students' understanding of core immunology and microbiology concepts in a course focused on foundational science concepts for a clinical practice course.MethodsThree cohorts of first-year medical students (n = 375) participated in a collaborative concept mapping team-based learning activity (CCM-TBL) involving HIV and the opportunistic pathogen, P. jirovecii. The CCM-TBL was utilized in place of the application questions in a traditional TBL. A voluntary seven-question Likert-scale survey was offered to students to capture their perspective on the utility of the activity. Three open-ended questions captured opinions regarding whether the activity helped them identify strengths and weaknesses related to the concepts. The concept maps were evaluated to determine the depth of student team understanding and employed Fisher's Exact Test and Cohen's kappa. Qualitative evaluation of the student survey responses was conducted. Quantitative data were statistically analyzed using descriptive statistics, Kruskal-Wallis, Mann-Whitney, and Cronbach's alpha.ResultsStudents successfully integrated multiple concepts, with a mode of 5 concepts per map. A survey of the perceptions of 130 students showed that most found CCM-TBL helped them identify weaknesses in immunology (76%) and microbiology (66.4%), and improved their understanding of immunology (76%), microbiology (70.6%), opportunistic infections (65.5%), and interactions between innate and adaptive immune responses (64.2%). However, only 57.8% endorsed concept maps as suitable for a TBL. After implementing feedback-based improvements, more students reported that the activity increased their understanding of immunology (p = 0.018) and microbiology (p = 0.032).DiscussionCCM-TBL appears to help reinforce and integrate foundational immunology content for first-year medical students.